(untitled) (Archaeologia Adriatica, 2023)
The paper presents results of a trial excavation of two stone-cairns located in the area of Krivodol near Trilj in the Cetina valley. Both cairns showed traces of prior ilegitimate excavation, and looting of the graves. Despite that during our excavation we discovered some intact cist graves with skeletal remains in them. Preliminary analyisis of those skeltal remains are also given in the paper. Well preserved samples enabled us to conduct C14 dating, which placed the graves into the 2nd millennium B. C. E.